A model for talent identification and development for team sports in South Africa - Hugo, K. (2004)
The purpose of this study was to investigate the influence of participation in a special squad-based talent development programme on selected physical variables and skills in adolescent girls. This investigation was initiated in the team sport of netball in order to determine if participation in a talent development programme of this kind can be successful in the South African context. A second purpose was to consider the effectiveness of the squad-based model in relation to the traditional school-based model that is commonly implemented for talent development in South African netball. This study followed a static group design in a field setting. The squad-based group (N=22) was composed of netball players ages 14 - 18 years old from two senior high schools in a previously disadvantaged community. The school-based group (N=45) was composed of netball players from the first and second teams at three schools in the same region, that maintained a good standard of netball and had qualified coaches. The subjects in the squad-based group participated in a special eight-month training programme, which consisted out of 2 training sessions (90minutes) and 1 match per week. The subjects in the school-based group participated in their normal pattern of netball practices and school matches. The results of this study lead to some general conclusions about the squadbased training model: • Four components of skill development improved significantly • Significant changes were found in four of the physical variables associated with netball performance. The squad-based model appeared to have been significantly more effective than the school-based model in the development of the physical variables of flexibility, speed, throwing velocity and aerobic fitness.Based on the results the squad-based model is proposed as an approach to talent development that can make a significant contribution to the development of skill. Continuous refinement of current models and even the creation of new models, may one day create systems where every child can reach toward his or her own sporting potential.